GC-MS Determination of Bioactive Components with Their Biological Activities of Olax subscorpioidea (Olacaceae) - Saidi Odoma; Ajibola Habeebulahi Adekilekun; Hope Onohuean; Funso-Babarimisa Funso; Adekilekun Habeebat Oyewusi; Abdulmumeen Amao Hamid (Biology, Medicine, & Natural Product Chemistry, 2025)
Medicinal plants have been an integral part of healthcare, particularly in Africa, where over 80% of the population relies on traditional herbal medicine. This research focuses on Olax subscorpioidea, a plant recognized for its extensive pharmacological activities, including anti-inflammatory, antioxidant, antidiabetic, and analgesic properties. The study aimed to identify the bioactive compounds present in the leaf extract of O. subscorpioidea using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The plant was collected, dried, and extracted with methanol, leading to the identification of 199 compounds, including phenols, terpenoids, flavonoids, and fatty acids, some of which possess significant biological activities. Toxicological studies indicated a safe dosage with no adverse effects observed in mice. This research underscores the potential of O. subscorpioidea as a source of novel therapeutic agents, necessitating further isolation and characterization of its bioactive constituents to explore their pharmacological potentials comprehensively.